Brief psychodynamic psychotherapies. Past, present, and future challenges - Kay, Jerald (American Psychiatric Press, Inc, 1997)
The future educational and research needs of brief psychodynamic psychotherapy are discussed. Specific shortcomings of current education and training in brief dynamic therapies are elucidated. Many of these are relevant to psychotherapy instruction in graduate medical education in nondynamic treatments as well. Educational and technological recommendations are suggested to remedy these shortcomings.